Emerging trends in the UK incidence of occupational asthma: should we be worried?. Issue 6 (1st April 2019) - Seed, Martin J; Carder, Melanie; Gittins, Matthew; Sen, Dil; Money, Annemarie; Fishwick, David; Barber, Chris M; van Tongeren, Martie
Abstract : While 15% of adult-onset asthma is estimated to have an occupational cause, there has been evidence of a downward trend in occupational asthma incidence in several European countries since the start of this millennium. However, recent data from The Health and Occupation Reporting network in the UK have suggested a possible reversal of this downward trend since 2014. We present these data and discuss possible explanations for this observed change in incidence trend. A high index of suspicion of occupational causation in new-onset asthma cases continues to be important, whether or not the recently observed increase in occupational asthma incidence in the UK is real or artefactual.